Genetic Evaluation Of Bangladesh Livestock Research Institute Cattle Breed-1 : Heritability And Genetic Correlation - Deb, GK; Mufti, MM; Mostari, MP; Huque, KS (Bangladesh Journal of Animal Science, 2012)
Heritability and genetic correlation of economic traits of Bangladesh Livestock Research Institute (BLRI) Cattle Breed-1 (BCB-1) were estimated with Residual Maximum Likelihood (REML) principle. The BCB-1 is a native cattle breed developed by BLRI through selective breeding among indigenous cattle of Bangladesh. Data asserted from performance record sheets of 500 animals maintained during 1992 to 2005 were analyzed for estimation of genetic parameters. The heritabilities were estimated with single trait animal model for age at service and age at first calving and those of single trait repeatability model for other traits. However, two traits animal models were used for estimation of genetic correlations among different traits. The model includes sex, season and year of birth, parity, generation and additive genetic merit of each individual. The estimated heritabilities were higher for lactation milk yield (LMY, 0.404) and age at first calving (AFC, 0.404) followed by moderate estimates of daily milk yield (DMY, 0.257), lactation length (LL, 0.333), peak milk yield (PMY, 0.335), milk yield per day of calving interval (MYCI, 0.227), age at first service (AFS, 0.316), calving interval (CI, 0.273), and post partum heat period (PPHP, 0.276). The genetic correlations of lactation milk yield were high with DMY (+0.797), LL (+0.797) and MYCI (+0.876), moderate with CI (+0.399), PPHP (+0.205) and DP (-0.404) and low with AFS (-0.048) and AFC (-0.025). The moderate to high heritabilities for along with high genetic correlations among most of the milk yield traits emphasized continuation of selective breeding program for maximization of genetic improvement of this breed. The information generated in the present study may also be used in planning breeding program for other indigenous cattle germplasm of the country. DOI: http://dx.doi.org/10.3329/bjas.v37i2.9878 BJAS 2008; 37(2): 25-33